Higher Water‐Splitting Performance of Boron‐Based Porous CoMnB Electrocatalyst over the Benchmarks at High Current in 1 m KOH and Real Sea Water (Adv. Sustainable Syst. 9/2022). (18th September 2022) - Lin, Shusen; Habib, Md Ahasan; Mandavkar, Rutuja; Kulkarni, Rakesh; Burse, Shalmali; Chung, Young‐Uk; Liu, Changsheng; Wang, Zilin; Lin, Shiwei; Jeong, Jae‐Hun; Lee, Jihoon
Abstract : Water Splitting In article number 2200213, Jihoon Lee and co‐workers demonstrate that porous CoMnB || CoMnB electrocatalyst show better water splitting performance than the benchmark electrodes of Pt/C || RuO2 at above 800 mA cm −2 with the cell voltage of 2.33 V in 1 m KOH, indicating a better H2 and O2 generation performance at the industrial operational condition in the high current range.